Coordination of efforts in disaster relief supply chains: the moderating role of resource scarcity and redundancy - Maghsoudi, Amin; Zailani, Suhaiza; Ramayah, Thurasamy; Pazirandeh, Ala (Taylor & Francis, 2018)
Connecting to the ongoing conversation on the importance of effective coordination, in this paper, we empirically examine the impact of key theoretical modes of coordination, i.e. resource sharing, standardisation of operations, and synchronisation in disaster relief supply chains, on the performance of the humanitarian organisations. Survey data are collected from 101 humanitarian organisations in the emerging countries within Southeast Asia. Data are used to test a conceptually developed model, using structural equation modelling–partial least square (SEM-PLS) approach. The results reveal the significant impact of resource sharing and standardisation on performance outcomes in terms of resources used, responsiveness, and flexibility, while resource sharing is highly weakened by resource scarcity and redundancy. The managerial implication and recommendations are concluded for further research.